2008
DOI: 10.1007/s00264-008-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic stem loosening in primary THA: migration analysis of cemented and cementless fixation

Abstract: Early migration has reportedly been predictive for later implant failure. Using four different migration patterns, this study aimed to analyse migration behaviour of the two types of implant fixation-cemented and cementlessthroughout the process of loosening. Migrational behaviour of 69 revised stems (49 cemented, 20 uncemented) was analysed retrospectively with EBRA-FCA (Einzel-BildRöntgen-Analyse, Femoral Component Analysis). Uncemented stems failed after early and late onset migration alike, while late migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 21 publications
4
32
0
3
Order By: Relevance
“…5). This finding is consistent with those of a previous study in which a decrease in the sensitivity of early migration as a predictor of later failure in the long term was reported [20]. Implants with late aseptic failure rarely showed early-onset migration and would not have been detected even by a very low migration threshold.…”
Section: Discussionsupporting
confidence: 83%
“…5). This finding is consistent with those of a previous study in which a decrease in the sensitivity of early migration as a predictor of later failure in the long term was reported [20]. Implants with late aseptic failure rarely showed early-onset migration and would not have been detected even by a very low migration threshold.…”
Section: Discussionsupporting
confidence: 83%
“…Using a lower threshold of 1.5 mm, 29 of 81 stems in our study were considered to have substantial migration, with 14 of the stems having more than 3 mm of migration. Other groups have used EBRA-FCA to study femoral component migration (Table 5), with our overall rate of migration observed with the Accolade 1 stem higher than other stem designs [6,15,29]. In particular, both Radl et al [38] and Kroell et al [29] showed early migration assessed with EBRA-FCA predicted poor long-term clinical performance when greater than 1.5 mm, mirroring the earlier work of Kobayashi et al [26] and Donnelly et al [10].…”
Section: Discussionsupporting
confidence: 73%
“…Other groups have used EBRA-FCA to study femoral component migration (Table 5), with our overall rate of migration observed with the Accolade 1 stem higher than other stem designs [6,15,29]. In particular, both Radl et al [38] and Kroell et al [29] showed early migration assessed with EBRA-FCA predicted poor long-term clinical performance when greater than 1.5 mm, mirroring the earlier work of Kobayashi et al [26] and Donnelly et al [10]. However, we must be careful in the interpretation of any migration study in regard to what represents the true threshold of migration leading to revision.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors concluded initial subsidence does not always lead to early revision [20]. A similar study by Kroell et al [24] also evaluated the migration patterns of cemented and cementless stems. In contrast to the study by Krismer et al [20], all the stems evaluated were ultimately revised.…”
Section: Discussionmentioning
confidence: 88%